Boosting Cholesterol Efflux from Foam Cells by Sequential Administration of rHDL to Deliver MicroRNA and to Remove Cholesterol in a Triple‐Cell 2D Atherosclerosis Model. Issue 13 (13th February 2022) - Jebari‐Benslaiman, Shifa; Uribe, Kepa B.; Benito‐Vicente, Asier; Galicia‐Garcia, Unai; Larrea‐Sebal, Asier; Santin, Izortze; Alloza, Iraide; Vandenbroeck, Koen; Ostolaza, Helena; Martín, César
Abstract: Cardiovascular disease, the leading cause of mortality worldwide, is primarily caused by atherosclerosis, which is characterized by lipid and inflammatory cell accumulation in blood vessels and carotid intima thickening. Although disease management has improved significantly, new therapeutic strategies focused on accelerating atherosclerosis regression must be developed. Atherosclerosis models mimicking in vivo‐like conditions provide essential information for research and new advances toward clinical application. New nanotechnology‐based therapeutic opportunities have emerged with apoA‐I nanoparticles (recombinant/reconstituted high‐density lipoproteins, rHDL) as ideal carriers to deliver molecules and the discovery that microRNAs participate in atherosclerosis establishment and progression. Here, a therapeutic strategy to improve cholesterol efflux is developed based on a two‐step administration of rHDL consisting of a first dose of antagomiR‐33a‐loaded rHDLs to induce adenosine triphosphate‐binding cassette transporters A1 overexpression, followed by a second dose of 1, 2‐dipalmitoyl‐sn‐glycero‐3‐phosphocholine rHDLs, which efficiently remove cholesterol from foam cells. A triple‐cell 2D‐atheroma plaque model reflecting the cellular complexity of atherosclerosis is used to improve efficiency of the nanoparticles in promoting cholesterol efflux. The results show that sequential administration of rHDL potentiates cholesterol efflux indicating that this approach may be used in vivo to more efficiently target atherosclerotic lesions and improve prognosis of the disease. Abstract : Cardiovascular disease, the leading cause of mortality worldwide, is primarily caused by atherosclerosis. Although disease management has improved significantly, new therapeutic strategies are needed. An efficient two‐step administration of nanoparticles is shown here to deliver antagomiR‐33a and to boost cholesterol efflux. This approach may be used in vivo to target atherosclerotic lesions more efficiently and improve prognosis of the disease.